2020
DOI: 10.1093/biolinnean/blaa132
|View full text |Cite
|
Sign up to set email alerts
|

Severe fires alter the outcome of the mutualism between ants and a Neotropical savanna tree

Abstract: Physical disturbances, such as fire, may affect the relationship between ants and plants. We evaluated the extent to which severe fires alter the protective effect of ants against the herbivores of an extrafloral-nectary bearing tree. We performed an ant removal experiment and sampled the ant fauna from the same trees over 4 years: the pre-fire year, the fire-year, and again 1 and 2 years later. Ants reduced insect herbivory in the pre-fire year and in the fire-year but failed to provide any plant protection i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…For example, in our review, we identified that most studies dealing with anthropogenic or with an unknown fire origin (i.e., type of fire) usually did not report fire frequency or any other aspect of the fire regime, such as fire severity. In contrast, the majority of publications that reported some aspects of the fire regime studied prescribed fires (see Massad et al, 2015; Paolucci et al, 2016; Vasconcelos et al, 2020 as examples). Therefore, given that the information about the fire regime is of crucial importance to better understand fire effects on global biodiversity (Bowman et al, 2016) and that different fire regimes differently impact organisms, we argue that some fire parameters such as type of fire, frequency, severity, intensity, and flame height must be informed in future studies to allow a deeper evaluation and a wider perspective of the fire effects on plant–animal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in our review, we identified that most studies dealing with anthropogenic or with an unknown fire origin (i.e., type of fire) usually did not report fire frequency or any other aspect of the fire regime, such as fire severity. In contrast, the majority of publications that reported some aspects of the fire regime studied prescribed fires (see Massad et al, 2015; Paolucci et al, 2016; Vasconcelos et al, 2020 as examples). Therefore, given that the information about the fire regime is of crucial importance to better understand fire effects on global biodiversity (Bowman et al, 2016) and that different fire regimes differently impact organisms, we argue that some fire parameters such as type of fire, frequency, severity, intensity, and flame height must be informed in future studies to allow a deeper evaluation and a wider perspective of the fire effects on plant–animal relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Por exemplo, em nossa revisão, identificamos que a maioria dos estudos que tratavam de fogo antropogênico ou de origem desconhecida (ou seja, tipo de fogo) geralmente não informava a frequência do fogo ou qualquer outro aspecto do regime de fogo, como a severidade do fogo. Por outro lado, a maioria das publicações que relataram alguns aspectos do regime do fogo estudou fogos prescritos (consulte Massad et al, 2015; Paolucci et al, 2016; Vasconcelos et al, 2020 como exemplos). Portanto, considerando que as informações sobre o regime de fogo são de importância crucial para entender melhor os efeitos do fogo na biodiversidade global (Bowman et al, 2016) e que diferentes regimes de fogo afetam os organismos de forma diferente, argumentamos que alguns parâmetros do fogo, como tipo de fogo, frequência, severidade, intensidade e altura da chama, devem ser informados em estudos futuros para permitir uma avaliação mais profunda e uma perspectiva mais ampla dos efeitos do fogo nas relações planta‐animal.…”
Section: Discussionunclassified
“…According to Knoechelmann and Morais (2008), under frequent fire, the presence of ants became greater in plants of S. adstringens in comparison with plants that grew in areas without fire; in particular, the abundance of Camponotus became higher after defoliation caused by fire. According to Rosa et al (2021), intense fire strongly changes the composition of ant species that nest exclusively in trees because they can die, thus reducing the efficiency of protection (Vasconcelos et al, 2020). However, for Camponotus ants, which were observed in S. adstringens , a high mortality is not frequent after moderate fires as demonstrated by Knoechelmann & Morais (2008).…”
Section: Discussionmentioning
confidence: 99%
“…However, Alves‐Silva & Del‐Claro (2014) demonstrated that, in this specific case, the ants failed to protect regrowth leaves from sucking herbivorous insect attacks because these sucking insects also provided those ants with sugary secretions such as the nectar secreted by the EFNs. On the other hand, in Crematogaster brasiliensis , ants reduced herbivory prior to and immediately after the fire, even though they failed in the protection after two years following the fire event (Vasconcelos et al, 2020).…”
Section: Discussionmentioning
confidence: 99%